Prevalence and pattern of cognitive impairment in rural and urban populations from Northern Portugal - Nunes, Belina (BioMed Central, 2010)
BACKGROUND: Despite worldwide recognition of the burden of dementia, no epidemiological data is yet available in Portugal. The objective of this study is to estimate the prevalence and describe the pattern of cognitive impairment with dementia or no dementia (CIND) in rural and urban populations from Northern Portugal. METHODS: Two random samples of residents aged 55 to 79 years in rural and urban communities were drawn from the health centres registries to be screened for cognitive impairment. The screening criteria for dementia were an abnormal Mini-Mental State Examination (MMSE) score or a Blessed Dementia Scale score. After excluding those who tested positive for dementia, cut-off points for CIND were set at 1 standard deviation below the mean of the MMSE according to educational level. All those who screened positive either for dementia or CIND were examined by a neurologist for establishing a definitive diagnosis. RESULTS: The prevalence of cognitive impairment was higher in rural than in urban populations, 16.8% (95% CI: 14.3-19.8%) vs. 12.0% (95%CI: 9.3-15.4%), with a rural/urban prevalence ratio (PR) of 2.16 (95% CI: 1.04-4.50) in the eldest and 2.19 (95% CI: 1.01-4.76) in persons with vascular risk factors. The prevalence of dementia was 2.7% (95% CI: 1.9-3.8%) with a rural/urban PR = 2.1 and the prevalence of CIND was 12.3% (95% CI: 10.4-14.4%) and PR = 1.3. The prevalence of dementia increases exponentially with age and in those with cerebrovascular disease or other comorbid conditions while the prevalence of CIND, besides these factors, is also higher in persons with low levels of education or vascular risk factors. Alzheimer's and vascular disease were equally likely aetiologies of dementia (38.7%), the later more common in men PR(F:M = 0.3) as opposed to the former PR(F:M = 2.0). Vascular CIND, associated either with cerebrovascular disease or vascular risk factors was more frequent (39.7%) then depression (18.4%) or any other aetiology. CONCLUSIONS: The prevalence of cognitive impairment is higher in rural compared with urban populations. This is shown in the synergy between age and rurality, with the rural/urban prevalence ratio increasing with age. In this relatively young population from Northern Portugal, cerebrovascular disease as well as vascular risk factors account for 48% of overall cognitive impairment.